Pharmaceuticals and Personal-Care Products in Plants - Bartrons, Mireia; Peñuelas, Josep (Trends in plant science, 2017)
Pharmaceuticals and personal-care products (PPCPs) derived from agricultural, urban, and industrial areas accumulate in plants at concentrations (ng to μg kg−1) that can be toxic to the plants. Importantly, the dietary intake of these PPCP-contaminated plants may also pose a risk to human health, but currently little is known about the fate of PPCPs in plants and their effect on or risk to the ecosystem. In this Opinion article we propose that in-depth research on the use of plants as a monitoring device for assessing the use and environmental presence of PPCPs is warranted. The toxicity of PPCPs to plants and their microbiota needs to be established, as well as any toxic effects on herbivores including humans. PPCPs derived from municipal, agricultural, and industrial wastewater are frequently detected anthropogenic contaminants in the environment. Plants take up, accumulate, and metabolize PPCPs at concentrations that can be toxic to plants, plant microbiota, and soil microorganisms, affecting plant–microorganism symbiosis. The dietary intake of these PPCP-contaminated plants may pose a risk to ecosystems and humans. Owing to the lack of data on the fate of PPCPs in the environment and their toxicity to plants and humans, no regulations exist for most PPCPs in irrigation water, biosolids, or manure before these are reused for agriculture or in supplies of drinking water, vegetables, and other food to be commercialized.